Consensus on MR Imaging of Endolymphatic Hydrops in Patients With Suspected Hydropic Ear Disease (Meniere) - Liu, Yupeng; Pyykkö, Ilmari; Naganawa, Shinji; Marques, Pedro; Gürkov, Robert; Yang, Jun; Duan, Maoli (Frontiers in Surgery, 2022)
Endolymphatic hydrops (EH) is considered the histological hallmark of Meniere’s disease. Visualization of EH has been achieved by special sequences of inner ear magnetic resonance imaging (MRI) with gadolinium-based contrast-agent via intravenous or intratympanic administration. Although it has been applied for more than ten years since 2007, a unified view on this technique has not yet been achieved. This paper presents an expert consensus on MRI of endolymphatic hydrops in the following aspects: indications and contra-indications for patient selection, methods of contrast agent administration (intravenous or intratympanic), MRI sequence selection, the specific scanning parameters settings, and standard image evaluation methods and their advantages and disadvantages. For each part of this consensus, a comment is attached to elucidate the reasons for the recommendation.